The Role of Pharmacists in Fulfilling Patient Rights in Obtaining Drug Services based on Permenkes Number 31 of 2016 concerning Amendments to Permenkes Number 889/Menkes/Per/V/2011 concerning Registration, Practice Permits, and Work Permits for Pharmacists - Chasanah, Khuswatun; Yustina, Endang Wahyati; Prabowo, Agus (Universitas Katolik Soegijapranata Semarang, 2023)
Pharmaceutical services are a form of service and the direct responsibility of pharmacists in pharmaceutical work. Pharmacists providing drug services have the knowledge and competence so that the patient's rights can be fulfilled. Researchers want to get an overview of the role of pharmacists in fulfilling patients' rights to obtain drug services based on Permenkes number 31 of 2016.This research uses qualitative methods with a sociological juridical approach. This research is analytical descriptive research conducted by taking samples in the Banyumas area. The sampling method uses a purposive sampling method. The research used a library field study data collection method. The data collected was analyzed qualitatively by laws and regulations.The legal basis for regulation regarding the role of pharmacists in fulfilling patient rights in obtaining drug services is contained in the 1945 Constitution, the Health Law, the Health Personnel Law, and PP concerning Pharmaceutical Work. The form of regulation is outlined in the Government Regulation concerning pharmaceutical service standards in pharmacies, the Minister of Health concerning amendments to the Minister of Health concerning registration, practice permits, and work permits for pharmacists. The implementation of the pharmacist's role in fulfilling patient rights in obtaining drug services in Banyumas Regency is by statutory provisions. Patients receiving drugs are given drug information regarding the rules for using and using drugs carried out by pharmacists. The purpose of implementing the pharmacist's role itself is to increase patient adherence to drug use.